Dynamic Capability, Knowledge Management, Organization Agility and Innovation on Competitive Performance of MSMEs in Batam City - Nurjanah, Listia; Thai, Kristina (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2025)
This research This study aims to identify the factors influencing Competitive Performance in MSMEs, which has become increasingly crucial considering the significant challenges faced by MSMEs due to the impact of the COVID-19 pandemic, such as declining demand, difficulties in sourcing raw materials, and growing competition in the digital era. The population of this study consists of managers and business owners in Batam City, Indonesia, with a total of 260 respondents. The data analysis in this study employs quantitative analysis by distributing questionnaires to managers and business owners in Batam City, Indonesia, and conducting hypothesis testing. The results of this study indicate that Dynamic Capability has a significant effect on Competitive Performance, Dynamic Capability has a significant effect on Organizational Agility, Innovation has a significant effect on Competitive Performance, and Knowledge Management has a significant effect on Competitive Performance. Furthermore, Knowledge Management has a significant effect on Dynamic Capability, Knowledge Management has a significant effect on Innovation, and finally, Organizational Agility has a significant effect on Competitive Performance.